Marked changes in electron transport through the blue copper protein azurin in the solid state upon deuteration - Amdursky, Nadav (National Academy of Sciences, 2013)
Measuring solid-state electron transport (ETp) across proteins allows studying electron transfer (ET) mechanism(s), while minimizing solvation effects on the process. ETp is, however, sensitive to any static (conformational) or dynamic (vibrational) changes in the protein. Our macroscopic measurements allow extending ETp studies to low temperatures, with the concomitant resolution of lower current densities, because of the larger electrode contact areas. Thus, earlier we reported temperature-independent ETp via the copper protein azurin (Az), from 80 K until denaturation, whereas for apo-Az ETp was temperature dependent above 180 K. Deuteration (H/D substitution) may provide mechanistic information on the question of whether the ETp involves H-bonds in the solid state. Here we report results of kinetic deuterium isotope effect (KIE) measurements on ETp through holo-Az as a function of temperature (30–340 K). Strikingly, deuteration changed ETp from temperature independent to temperature dependent above 180 K. This H/D effect is expressed in KIE values between 1.8 (340 K) and 9.1 (≤180 K). These values are remarkable in light of the previously reported inverse KIE on ET in Az in solution. We ascribe the difference between our KIE results and those observed in solution to the dominance of solvent effects in the latter (larger thermal expansion in H(2)O than in D(2)O), whereas in our case the KIE is primarily due to intramolecular changes, mainly in the low-frequency structural modes of the protein caused by H/D exchange. The observed high KIE values are consistent with a transport mechanism that involves through-H-bonds of the β-sheet structure of Az, likely also those in the Cu coordination sphere.